Editorial: Towards energy efficient and sustainable transportation networks - Aguiléra, Vincent; Seidowsky, Régine (European Journal of Transport and Infrastructure Research, 2014)
This special issue of the European Journal of Transport and Infrastructure Research comprises six papers, with a focus on energy efficiency and sustainability in transportation networks. Preliminary versions of those papers were presented during the EWGT 2012 Conference, the 15th meeting of the Euro Working Group on Transportation. The contributions have been selected to reflect the diversity of topics and approaches presented during the conference. They have been substantially extended by their respective authors and carefully reviewed and revised; this special issue contains the final selection of accepted papers. The editors are grateful to the authors and referees for their prompt and careful collaboration during the preparation of this special issue. This editorial first provides a few additional words about the Euro Working Group on Transportation and about the EWGT 2012 Conference, and then presents the selected contributions.